FORMATION OF INFORMATION LITERACY OF PRIMARY SCHOOL STUDENTS - Сартаева, Назгуль; Uaidullakyzy, Elmira; Zhumagul, Malika; Tolegenov, Bakyt; Kerimbayeva, Dinara (Pedagogy and Psychology, 2023)
Today, the rapid pace of development of society leads us to a confluence with a huge flow of information. Information is becoming more and more extensive in any area. Of particular importance is the wide amount of information at the initial stage of Education, which forms the Future Foundation of a person, the relevance of the formation of Information Culture, Information Literacy, which is necessary for students of primary school age to regulate their attitude to them, its correct application. Information literacy allows you to orient yourself in the information world, change direction, adapt to changes in information tasks. It is also made up of intellectual skills such as analysis, goal setting, decision making, observation and evaluation that are used in the act of thinking. From this point of view, this topic requires careful research. The purpose of the article is to consider the theoretical problems of the formation of information literacy of Primary School students, to present its effective ways, methods based on the results of experiments. To achieve the goal of the study, the following tasks were set: to analyze the concept of "information literacy" and give a definition of the concept; to determine the level of formation of information literacy of Primary School students; to reveal the main criteria and components on this issue; to propose effective ways to form information literacy of Primary School students. In the article, the skills representing the concept of "information literacy" are considered as its indicator, and the levels of development are differentiated. It is concluded that the information literacy of a person is a set of his motives, knowledge, skills and abilities that allow him to analyze complex processes of information flow. Keywords: information, information literacy, component, motivation, information activity.